1976
DOI: 10.1107/s0567740876009163
|View full text |Cite
|
Sign up to set email alerts
|

α-V1.08P0.92O5 at 22°C

Abstract: Abstract. oc-Vl.os(1)Po.9205, tetragonal, P4/n; a = 6.011 (4), c=4.452 (4) A; Z=2, Dealt=3"39 gcm -3, 147 independent reflexions. The structure was refined by full-matrix least-squares methods, R=0.076, with scintillation counter-measured intensities and monochromatized Mo K~ radiation. The composition was determined by varying the occupancy of the tetrahedral site. The vanadyl bond length is 1.578 (9) /k. Unlike stoichiometric 0c-VPO5 no evidence of positional disorder was found.Introduction. Crystals were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…The VO 4 were expected to behave such as the VO 4 or PO 4 in a special form [16] of α-VOPO 4 , thus, VO 4 with four overbonded uniform bonds. Hence, the VO 5 units must exist as VO 5 + 1 with V=O and V···O bonds and underbonded V-O bonds.…”
Section: Changes Of V-o Distancesmentioning
confidence: 99%
See 2 more Smart Citations
“…The VO 4 were expected to behave such as the VO 4 or PO 4 in a special form [16] of α-VOPO 4 , thus, VO 4 with four overbonded uniform bonds. Hence, the VO 5 units must exist as VO 5 + 1 with V=O and V···O bonds and underbonded V-O bonds.…”
Section: Changes Of V-o Distancesmentioning
confidence: 99%
“…Numerous structures of related crystals of the VPG system are reported [16,[20][21][22][23][24][25][26][27][28]. Some of the structural parameters are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highly active and selective (VO) 2 P 2 O 7 catalyst has the optical basicity K = 0.49 [33]. Since Ag + ions (K = 1.25 for [20,22,36,38,39].…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] This opens the possibility that the V +5 sites responsible for alkane and furan activation may come from the small amounts of VOPO4. [20] As a result, we considered three phases of VOPO4: αΙ, [21] αΙΙ, [22] and the proposed X1-phase. [23,24] We found that…”
Section: Reactivity Of Vopo4 Toward N-butane C-h Activationmentioning
confidence: 99%